A common fixed point of weakly compatible mappings in dislocated metric space - Panthi, D; Jha, K (Kathmandu University Journal of Science Engineering and Technology, 2013)
The purpose of this paper is to establish a common fixed point theorem for pairs of weakly compatible maps in dislocated metric space which generalizes and improves similar fixed point results. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 25-30